Different proteomic profiles of cinnabar upon therapeutic and toxic exposure reveal distinctive biological manifestations. (10th May 2020) - Yang, Mimi; Wang, Lichao; Zhang, Tao; Zhu, An; Sun, Yuqing; Zhao, Jingwei; Liu, Dan; Wang, Qi; Zeng, Kewu
Abstract: Ethnopharmacological relevance: Cinnabar, a traditional Chinese mineral medicine with sedative and tranquilizing effects, is known to be toxic to the neural system, but its detailed pharmacological and toxicological mechanisms are still unclear. Aim of the study: This study aimed to explore the potential neuropharmacological and neurotoxicological mechanisms of cinnabar by investigating the differentially expressed proteins in cerebral cortices of mice exposed to therapeutic and toxic doses of cinnabar. Materials and methods: Label-free quantitative proteomics and bioinformatics analysis were used to characterize the proteins, pathways, and potential targets associated with therapeutic (50 mg/kg) and toxic (1000 mg/kg) doses of cinnabar in cerebral cortices of mice. Proteomic analysis was verified by parallel reaction monitoring. Results: A total of 6370 and 6299 proteins were identified in the cerebral cortices of mice after exposure to therapeutic and toxic doses of cinnabar, among which 130 and 119 proteins were differentially expressed, respectively. Functional/pathway enrichment analysis showed that both exposure doses of cinnabar could affect transport processes in the cerebral cortex through different proteins. The changes induced by the therapeutic dose included pathways involved in translation and sphingolipid metabolism. Interestingly, for the toxic dose, differentially expressed proteins were enriched for functions and pathways related to RNA splicing, transcription, synaptic plasticity regulation and developmental processes, among which RNA splicing was the most significantly affected function. ATP6V1D and CX3CL1 were shown to be possible key proteins affected by cinnabar, leading to multiple functional changes in the cerebral cortex at the therapeutic and toxic doses, respectively. Furthermore, Connectivity Map (CMap) analysis predicted LRRK2 to be a potential therapeutic target and FTase to be a potential toxic target for cinnabar. Conclusion: Our results suggest that the pathways and potential targets identified in the mouse cerebral cortex exposed to therapeutic and toxic doses of cinnabar are different, which provides novel insights into the potential molecular mechanisms underlying the pharmacological and toxicological effects of cinnabar. Graphical abstract: Image 1 Highlights: ∙ The differentially expressed proteins, pathways in the mouse cerebral cortex exposed to therapeutic and toxic doses of cinnabar were identified. ∙The possible key proteins effected by therapeutic and toxic doses of cinnabar were speculated. ∙The potential therapeutic and toxic targets for cinnabar were predicted. ∙There might be different molecular mechanisms underlying the pharmacological and toxicological effects of cinnabar.